Pengaruh Media Sosial Tik Tok terhadap Gaya Komunikasi Siswa SDN 18 Kinali Kabupaten Pasaman Barat Provinsi Sumatera Barat - Yoana Lestonac Elita Wumbu (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2021)
The main problem in this research is the inflience of Tik Tok social media on communication style at SDN 18 Kinali, Tiktok is an audio-visual media contains photos and videos that spread creativity and uniqueness of each user. Moreover, Tiktok always provides unique and interesting special effects that can be used by every user. This social media can make users feel happy because the videos they make can be accompanied by a variety of trending and contemporary music. In using Tik Tok it self, many students use it not only once or twice a day. As of the purpose of the problem in this study is how the effect of outside world such as tiktok in building children’s character on their communication style to older people and also to the environment. This study is a quantitative research in the form of survey methods, the data collection is carried out by distributing some questionnaires to 167 students in which the filling of the questionnaires will be accompanied by their parents. The result of this survey indicates that there is a very significant positive effect from Tiktok on communication style. This is in accordance with the researcher calculation by using Microsoft Excel 2010, make use of correlation test which obtained a value of t(count) > t(table) that is 7.091 > 1.656, means that the more social media available, the more communication style will increase.